The Relationship Between Pregnant Women's Knowledge of Prenatal Massage and Anxiety Reduction During Pregnancy at Alisah Clinic in 2025 - Eni Monaliska Sihombing (PT Inovasi Pratama Internasional, 2025)
Health is a state of complete physical and psychological well-being that enables every individual to live a socially and economically productive life. Pregnancy is a period that begins at conception and lasts until the birth of the fetus. During pregnancy, many changes occur, both physical and psychological, one of which is anxiety. One type of massage that can be applied during pregnancy to reduce anxiety is prenatal massage. The objective of this study was to determine The Relationship Between Pregnant Women's Knowledge About Prenatal Massage and the Reduction of Anxiety During Pregnancy at Alisah Clinic in 2025. This research used an analytic survey method with a cross-sectional approach. The population in this study consisted of 35 pregnant women. The sampling technique used was total population sampling, where the entire population was taken as the sample, totaling 35 people. The results showed that the majority of respondents had poor knowledge about prenatal massage, totaling 31 people (88.6%), while the minority had good knowledge, totaling 2 people (5.7%). The majority of mothers did not experience reduced anxiety, totaling 28 people (80%), while the minority experienced reduced anxiety, totaling 7 people (20%). There is a significant relationship between pregnant women's knowledge about prenatal massage and the reduction of anxiety during pregnancy at Alisah Clinic in 2025, as indicated by a Sig. value of 0.000 < α 0.05. The conclusion of this study is that there is a significant relationship between pregnant women's knowledge about prenatal massage and the reduction of anxiety during pregnancy at Alisah Clinic in 2025. It is recommended that mothers increase their knowledge, particularly about prenatal massage, in order to reduce anxiety during pregnancy